Usefulness of mycophenolic acid monitoring with PETINIA for prediction of adverse events in kidney transplant recipients. (18th May 2016) - Ham, Ji Yeon; Jung, Hee-Yeon; Choi, Ji-Young; Park, Sun-Hee; Kim, Yong-Lim; Kim, Hyung-Kee; Huh, Seung; Kim, Chan-Duck; Won, Dong IL; Song, Kyung Eun; Cho, Jang-Hee
Abstract: Background Therapeutic drug monitoring of mycophenolic acid (MPA) is required to optimize the immunosuppressive effect and minimize toxicity. We validated a new particle-enhanced turbidimetric inhibition immunoassay (PETINIA) for the determination of MPA levels and evaluated the relationship of MPA trough level with drug-related adverse events.Methods PETENIA and liquid chromatography-mass spectrometry (LC-MS) were used to determine MPA concentrations from 54 kidney transplant recipients (KTRs). Agreement between PETINIA and LC-MS results was assessed by Passing-Bablok regression and the Bland-Altman plot method. The association of adverse events with MPA trough level obtained by PETINIA was analyzed.Results PETINIA revealed a good agreement with the LC-MS; Regression analysis gave an equation of y = 1.27x − 0.12 ( r 2  = 0.975, p  < 0.001). PETINIA showed a systemic positive bias with a mean difference of 0.66 mg/L compared to LC-MS. However, the magnitude of the positive bias decreased to 0.44 mg/L within the therapeutic range of MPA. Multiple logistic regression showed that MPA trough level determined by PETINIA was an independent risk factor for adverse events (odds ratio 2.28, 95% CI 1.25–4.16, p  = 0.007). MPA trough level predicted adverse events with a sensitivity of 77.8% and a specificity of 86.7% using a cut-off level of 5.25 mg/L.Conclusions Good correlation between the two methods indicates that PETINIA is an acceptable method for the monitoring of MPA therapeutic levels. Furthermore, MPA trough level obtained by PETINIA is a useful monitoring tool to minimize toxicity in KTRs.